2022
DOI: 10.1111/apa.16420
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of cognition in spina bifida and its consequences for activity and participation throughout life

Abstract: Spina bifida is caused by an incomplete closure of the neural tube during the first 3 weeks of pregnancy. The nerves, which are normally embedded in the spinal cord, develop in a hernia sac outside of the spinal cord and are unable to transmit impulses from the brain to extremities and organs below the area of the lesion. Depending on the placement of the hernia, the effects vary in terms of the level of paralysis, numbness and difficulties with bladder and bowel functions.In addition, spina bifida significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“… 15 From a public health standpoint, being about one standard deviation taller, by contrast, has been associated with better academic achievement (e.g., write skills), a characteristic that has been found altered in the pediatric population with SB. 16 Monitoring the height and BMI of participants with SB would support programs for preventing stunting and overweight in this population. It is important to note that interventions for improving growth outcomes have been recommended by several health agencies including the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“… 15 From a public health standpoint, being about one standard deviation taller, by contrast, has been associated with better academic achievement (e.g., write skills), a characteristic that has been found altered in the pediatric population with SB. 16 Monitoring the height and BMI of participants with SB would support programs for preventing stunting and overweight in this population. It is important to note that interventions for improving growth outcomes have been recommended by several health agencies including the World Health Organization.…”
Section: Discussionmentioning
confidence: 99%
“…It is recognized that almost 50% of those who enrolled in the study never wore the socks, indicating that adherence to sock wear was an issue. Linquist et al reported that people with SB have executive dysfunction which can significantly impact activities of daily living and autonomy [ 10 ]. This can contribute to barriers to participation.…”
Section: Discussionmentioning
confidence: 99%
“…Spina bifida is caused by incomplete closure of the neural tube during the first 3 weeks of pregnancy. A scoping review by Lindquist et al summarised the findings about cognitive characteristics in people with spina bifida 4 . This showed that the majority had cognitive difficulties and that these manifested in problems with language, perception, memory, executive and attentional functions.…”
Section: Scoping Review Of Cognition In Spina Bifida Highlights How I...mentioning
confidence: 99%
“…The Responses to Illness characteristics in people with spina bifida. 4 This showed that the majority had cognitive difficulties and that these manifested in problems with language, perception, memory, executive and attentional functions. These had a major impact on their daily life, which could affect medical adherence and responsibility and the ability to prevent secondary complications.…”
Section: Paediatric E Arly Warning Sys Tem For Hi G H -Ris K Maln Utr...mentioning
confidence: 99%